Effect of replacing soybean meal by urea on performance, carcass characteristics and meat quality of housed Saanen young goats - De Araujo Pimenta, José Luiz Leonardo [UNESP]; da Silva Filho, Carlos Alberto; de Macedo, Karine Bellas Romariz; da Rocha Olivieri de Barros, Rafaella; dos Santos Fonseca, Júlia; Maia, Arléia Medeiros; de Sousa, Sabrina Luzia Gregio; de Oliveira, Rodrigo Vasconcelos (Revista Brasileira de Ciencias Agrarias, 2020)
The aim of this study was to evaluate the effect of replacing soybean meal by urea in the diet of housed Saanen young goats on performance, carcass and meat characteristics. Eighteen Saanen young males were used, with an initial average weight of 21.68 ± 0.83 kg for the treatment with soybean meal and 20.89 ± 0.61 kg for the treatment with urea, distributed in a completely randomized design. The total weight gain and the slaughter weight, as well as the carcass and commercial cuts yield were not altered by the replacement of soybean meal with urea (p > 0.05). However, there was less fasting weight loss in the diet containing urea (p = 0.01). The meat quality characteristics were also not changed by the total substitution of soybean meal for urea (p > 0.05). The replacement of soybean meal with urea does not compromise the performance, carcass characteristics and the meat quality of housed Saanen young goats.
Keywords: Carcass yield; Commercial cuts; Morphometric measurements; Non-protein nitrogen; Rib-eye area